Inverse kinematics analysis of hydraulic support - LU Xuliang; YAN Haifeng; ZHANG Li (Gong-kuang zidonghua, 2018)
For problem that existing forward kinematics analysis methods of hydraulic support could not predict attitude of top beam accurately, an inverse kinematics analysis method of hydraulic support was put forward. 3D model and Motion model of hydraulic support were built by use of SolidWorks software and its Motion module. Motion database was obtained by analyzing motion of hydraulic support, and motion equation of each driving part in hydraulic support was fitted by use of cubic polynomial curve. Then the motion equations were optimized by use of particle swarm optimization algorithm to get the optimal motion equations, so as to obtain the optimal motion tracks of hydraulic support. The test result shows that the method can get motion track of each driving part of hydraulic support correctly, and the result is consistent with the actual one.